The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.brs.2017.01.142
|View full text |Cite
|
Sign up to set email alerts
|

Early and late onset depression in late life: a prospective study on clinical and structural brain characteristics and response to electroconvulsive therapy

Abstract: The clinical profile of late life depression is frequently associated with cognitive impairment, aging-related brain changes and somatic comorbidity. This two-site naturalistic longitudinal study aimed to explore differences in clinical and brain characteristics and response to electroconvulsive therapy (ECT) in early (EOD) versus late onset (LOD) late life depression (respectively onset < and ≥ 55 years). Methods Between January 2011 and December 2013, 110 patients aged 55 years and older with ECT treated uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…This leads to the hypothesis that WML may not be involved in the pathophysiology of severe LOD. Moreover, little differences were found between EOD and LOD in our cohort with severe LLD 20 indicating that age-at-onset may be an irrelevant specifier in severe depression.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…This leads to the hypothesis that WML may not be involved in the pathophysiology of severe LOD. Moreover, little differences were found between EOD and LOD in our cohort with severe LLD 20 indicating that age-at-onset may be an irrelevant specifier in severe depression.…”
Section: Discussionmentioning
confidence: 57%
“…These results are similar to our current findings and findings in our previous report, showing high ECT response rates in patients with severe LLD, high apathy scores, and WMH. 20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Research investigating age of depression onset as a predictor of treatment response has also reported contradictory results. 12 For example, several studies have found that early onset depression is associated with poorer treatment response, 13 slower remission, 14 and higher rates of recurrence 15,16 compared to late-onset depression.…”
Section: Introductionmentioning
confidence: 99%